Serial Fetal Heart Rate Monitoring During Electroconvulsive Therapy in Late Pregnancy: A Case Report of Transition From Succinylcholine to Rocuronium Reversed With Neostigmine - Katsuichiro Shimizu; Hiroyuki Muraoka; Tomoe Fujita; Kyoko Hattori; Taiyo Nishikawa; Hana Uchitsubo; Daigo Ochiai; Shunsuke Hyuga; Ken Inada (Neuropsychopharmacology Reports, 2026)
ABSTRACT Electroconvulsive therapy (ECT) is considered relatively safe and effective for severe psychiatric disorders during pregnancy, but evidence regarding neuromuscular blockers for ECT in pregnancy remains limited. We report a 30‐year‐old primigravida admitted at 30 weeks of gestation with severe major depressive disorder and persistent suicidal ideation despite pharmacotherapy. ECT was initiated at 32 weeks and 2 days of gestation. The first five sessions used succinylcholine. Owing to a nationwide shortage in Japan, the muscle relaxant was switched to rocuronium from the sixth session, with neostigmine and atropine used for reversal during the two antepartum rocuronium sessions. Serial cardiotocographic monitoring before and after each of the seven antepartum ECT sessions showed a transient decrease in fetal heart rate variability after ECT in all sessions and a transient increase in fetal heart rate baseline in five of the seven sessions (Sessions 1, 2, 3, 5, and 7), while fetal well‐being was maintained throughout. Spontaneous vaginal delivery occurred at 37 weeks and 0 days, five days after the seventh ECT session. The infant developed respiratory failure shortly after birth and required ventilatory support for two days, but subsequently recovered without complications. Postpartum ECT was resumed for five additional sessions using rocuronium reversed with sugammadex, and the patient achieved clinical remission. This case suggests the feasibility of rocuronium with neostigmine reversal as an alternative to succinylcholine for ECT during late pregnancy when succinylcholine is unavailable, provided that multidisciplinary management and fetal monitoring are available.